PEMBUATAN KOMPOS LIMBAH NENAS DENGAN MENGGUNAKAN BERBAGAI BAHAN AKTIVATOR - sriharti sriharti (Purifikasi, 2006)
In order to utilize pineapple waste, compost production is one of the alternatives. The compost can be used as soil conditioner. The compost was made in a plastic drum of 50 L capacity. Various activators were applied to speed up the composting process this experiment. The activators used were Green Phosko bioaktifator, EM4 and Agrisimba. Each treatment was performed three times. Results of this experiment showed that utilization of these activators had no significant influence to temperature, time of composting process and the product quality. Quality of the compost produced by using EM4 and Agrisimba activators met the Indonesian National Standard (SNI) for pH, moisture content, C-organic, total nitrogen, C/N ratio values, and P2O5, K2O, CaO, Fe, Mn, Zn concentrations. However, the compost produced by Green Phosko Bioactivator treatment did not meet the SNI for pH value, and MgO and Al concentrations.